Modeling Diffusion Effects for a Stepwise Two-Electron Reduction Process at a Microelectrode: Study of the Reduction of para-Quaterphenyl in Tetrahydrofuran and Inference of Fast Comproportionation of the Dianion with the Neutral Parent Molecule - Belding, SR; Baron, R; Dickinson, E; Compton, R (2009)
This paper presents a study of voltammetry at microdisc electrodes for a stepwise two electron reduction (A + 2e- ⇌B + e- ⇌C) where the relevant formal potentials of the A/B and B/C couples are such that two distinct voltammetric waves are seen. Simulations are used to explore quantitatively the effect of comproportionation (A + C → 2B) on the observed cyclic voltammetry and potential-step chronoamperometry. It is found that, in the limit of electrochemical reversibility, the presence of comproportionation can be discerned using cyclic voltammetry only at high scan-rates and when the diffusion coefficients of the species (Da, Db, and Dc) are significantly different, such that D B/DA > 1.5 and DC/DA > 1.5 or DB/DA < 0.75 and DC/DA < 0.75. The theory is used to provide clear evidence for diffusionally controlled comproportionation in the stepwise two electron reduction of para-quaterphenyl in the solvent THF. © 2009 American Chemical Society.